Ivan Goncharov - Lyngstad, Alexandra (Twayne Publishers, 1971)
Provides in-depth analysis of the life, works, career, and critical importance of Ivan Goncharov
Includes bibliographical references and index
Keywords: Goncharov; Ivan Aleksandrovich